The Product Characteristic of Electronic Money from the Perspective of the Negotiable Instruments Law - Geigiansyah Aulia Putra; Hilda Yunita Sabrie; Prawitra Thalib (Universitas Lampung, 2017)
The development of currency trading is not only using the cash as a payment instrument for a transaction. For example is the emergence of non-cash payments such as negotiable instruments. That type of instrument offers a more effective and safer way than using the cash. Along with the development of the technology, a non-cash payment innovation emerged, which characteristics, at a glance, similar to negotiable instruments, such as credit cards, debit cards, and electronic money products which gives a safer and more efficient way than using the cash for a transaction. Based on this, led to the view that non-cash payment instruments such as credit cards, debit cards, and electronic money products can be classified as negotiable instruments. However, that classification must be done by reviewing the relevant regulations, such as Commercial Code and else and also observing the doctrines in the perspective of the science concerned, to state that the development of such instruments can be classified as negotiable instruments or not.Keywords: Negotiable instruments, Letter of Value, Credit Cards, Debit Cards, Electronic Money Products, Classification.